PEMASANGAN ANTENA PENGUAT SINYAL (GSM) PADA KAMPUNG KAIBURSE - Muriani Muriani; Adik Putra Andika; Rapha Nichita Kaikatui (Musamus University, 2021)
Kaiburse village community has a Smart House facility that is used as a multipurpose buildingbecause all village activities are held centrally in the building, for example posyandu activities,student service learning activities and others. At this time in the location of the Smart House thequality of the HP signal network for telecommunications is very poor, so that people havedifficulty in accessing the telephone signal, because the distance is quite far from the location ofthe nearest BTS, with a distance of 7 kilometers in Kampung Kumbe. The installation of HandponeSignal Amplifiers (GSM) in the Kaiburse Kampung Smart House aims to support the activities ofthe village community, especially related to telecommunications needs. The Handpone (GSM)Signal Booster Antenna that we will use is the Yagi antenna. The results of this dedication activityare the quality of the HP signal received inside the smart home which is very good namely 5 Barrfor repeaters and 4 Barr for HP with excellent sound quality